Emerging Trends of Plant Physiology for Sustainable Crop Production - Abbas, PhD., Zafar; Tiwari, PhD., Ajay Kumar; Kumar, PhD., Pradeep; Apple Academic Press (Toronto ; New Jersey : Apple Academic Press, 2018)
Plant physiology is now considered as an essential ingredient for improving crop productivity, a continuing necessity with today$1 (Bs ever-increasing world population. This new volume provides an understanding of the physiological basis of the various plant processes and their underlying mechanisms under fluctuating environments, which is of great importance for sustainable crop production. Further advances in cellular and molecular biology hold promise to modify physiological processes, thereby improving the quality and quantity of major food crops and ensuring stability in yield of the produce even under severe abiotic stress. This book covers the latest information on the physiological basis of plant productivity, including abiotic stress adaptation and management, plant nutrition, climate change and plant productivity, transgenic and functional genomics, and plant growth regulators and their applications. The chapters in this volume tackle some of these key issues of sustainable plant production and evolve future strategies in overcoming challenges faced by the agricultural sector as a whole. The topics covered in this book presents important from research reputed scientists. This volume is a rich source of information in one place. It will be a useful resource for researchers and extension workers involved in plant physiology and related disciplines. Key features: Provide the latest information on developments in plant physiology. Covers abiotic and biotic stress on economically important crop species. Presents a detailed collection of biotechnological approaches in plant physiology. Covers plant growth regulators, secondary metabolites, germination, crop growth and development of different crop species. Provides research from experts at internationally renowned institutes.s
Potato Physiology in Relation to Crop Yield----Brajesh Singh, Maharishi Tomar, Som Dutt, Pinky Raigond, and B. P. Singh -- Phytochrome: Physiology, Molecular Aspects, and Sustainable Crop Production-- --Bandana Bose, Bhawna Pant, Rajesh K. Singhal, Mahesh Kumar, and Sananda Mondal -- --Signal Transduction in Plant with Response to Heavy Metals Toxicity: An Overview-- --Prasann Kumar -- Vegetable Oil and Its Significance in Sustainable Development----A. Hasnat -- SnRK1 (Sucrose Non Fermenting 1-RelatedKinase 1):A Key Player of Plant Signal Transduction----Bhavin S. Bhatt, Fenisha D. Chahwala, B. Singh, and Achuit K. Singh -- B-Vitamins inRelationto Sustainable Crop Productivity in Crop Plants----Anoop Kumar, Dildar Husain, Jagjeet Singh, Satya Pal Verma, and Zafar Abbas -- Mechanisms ofMetalloid Uptake, Transport, Toxicity, and Tolerance in Plants----Pallavi Sharma, Vineet Srivastava, Amit Kumar Gautam, Anisha Rupashree, Rajani Singh,Sanchita Abhijita, Satish Kumar, Ambuj Bhushan Jha, and Amarendra N. Misra -- Morpho-Physiological Responses of Wheat Genotypes under High-TemperatureStress----Sharad K. Dwivedi, Santosh Kumar, and K. K. Rao -- Control of Micro Biogenesis and Action in Plants----Mohd. Zahid Rizvi -- Mineral Nutrition in Plants and Its Management in Soil----Aneg Singh and A K Tiwari -- Supermolecular Organization of Photosynthetic Complexes inArabidopsis----Mohammed Sabar, Alexandre Marchal, David Joly, Sridharan Govindachary, Eric Bonneil, Pierre Thibaut, Robert Carpentier, and Normand Brisson-- Methods to Improve Germination in Sugarcane----S. P. Singh, Priyanka Singh, and B. L. Sharma -- Secondary Metabolites: The Plant PhysiologicalTale of Stress Response----R. K. Upadhyay -- Effect of Wastewater Irrigation on Crop Health in the Indian Agricultural Scenario----AbhijitSarkar, Sujit Das, Vaibhav Srivastava, Pooja Singh, and Rajeev Pratap Singh.
Includes bibliographical references and index.
Also available in print format.
Keywords: TECHNOLOGY & ENGINEERING / Agriculture / General; Plant physiology; Plant physiology -- Research; SCIENCE -- Life Sciences -- Anatomy & Physiology; Electronic books